Analisis Motivasi Kader Kesehatan dalam Penemuan Kasus Tuberkulosis di Wilayah Kerja UPTD Puskesmas Pengaringan Oku Tahun 2021 - Desi Andrianovita; Erma Gustina (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Tuberculosis is an infectious infectious disease caused by the Mycobacterium tuberculosis which mainly attacks the lungs. The purpose of this study was to determine what factors were associated with the motivation of health cadres in finding cases of tuberculosis in the working area of ??UPTD Puskesmas Pengaringan Kab. OKU 2021. The design of this research is Cross Sectional. The population in this study were health cadres in the work area of ??Pengaringan Health Center, Ogan Komering Ulu Regency in 2021. The sampling method in this study used a total sampling technique. The number of samples in this study were 70 respondents. Data collection by using a questionnaire. The results of the statistical analysis of respondents using the Chi-Square test showed that there was a significant relationship (p < 0.05) for age (0.001), cadre tenure (0.013), education (0.007), knowledge (P Value 0.009), attitude (P Value 0.004 ), training (P Value 0.000) and supervision (0.000). From the results of the multivariate analysis, the dominant factor on the motivation of cadres in finding Tuberculosis cases in the work area of ??the Pengaringan Health Center, Ogan Komering Ulu Regency in 2021, is Supervision (P Value 0.000) (OR 28.967). From this research, it is hoped that the Puskesmas will carry out periodic supervision and guidance to health cadres, forming special cadres who run DOTS programs, especially in finding Tuberculosis cases.